Manufacturer Strategies for Blockchain Adoption and Sales Mode Selection with a Dual-Purpose Platform - Lirong Wu; Congying Duan; Qingkai Ji (Systems)
This study examines how a low-carbon manufacturer strategically adopts blockchain technology and selects sales modes with a dual-purpose e-commerce platform that focuses on both profit and consumer surplus. We develop six game-theoretic models by combining three sales modes (agency, reselling, and dual modes) with two blockchain scenarios (adoption vs. non-adoption). Using backward induction, we derive equilibrium strategies for supply chain members and analyze the impacts of key parameters. Building on these analyses, we further investigate the joint decision-making of blockchain adoption and sales mode selection, exploring how the platform’s consumer surplus concern influences manufacturer decisions, and evaluating the economic value created by blockchain under alternative sales modes, ultimately leading to three key findings: (1) The agency mode is generally preferred in most cases, especially when the platform has a moderate level of concern for consumer surplus. Blockchain adoption is only recommended when its unit operational cost is below certain thresholds, and it can significantly impact the choice between agency and dual modes based on the platform’s consumer surplus concern. (2) Platform’s degree of consumer surplus concern exerts a negligible effect on manufacturer’s sales mode selection without blockchain, but it becomes crucial and can trigger a shift to the dual mode when blockchain is adopted. (3) Blockchain generates the greatest economic value for the manufacturer under the dual mode, regardless of cost thresholds. For platforms, the optimal strategy depends on blockchain’s unit operational cost, with the reselling mode being optimal for low cost and the agency mode preferred for higher cost.